2006
DOI: 10.1128/aem.01087-06
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Use and Resistance in Swine Waste Treatment Systems

Abstract: Chlortetracycline and the macrolide tylosin were identified as commonly used antimicrobials for growth promotion and prophylaxis in swine production. Resistance to these antimicrobials was measured throughout the waste treatment processes at five swine farms by culture-based and molecular methods. Conventional farm samples had the highest levels of resistance with both culture-based and molecular methods and had similar levels of resistance despite differences in antimicrobial usage. The levels of resistance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
88
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 31 publications
10
88
1
Order By: Relevance
“…Angenent et al (2008) reported an increase in MLS B resistance in an ASBR treating swine waste but attributed their results to the enrichment with resistant bacteria present in the reactor feed. Occurrence of macrolide resistant organisms in swine waste has been reported previously (Chen et al, 2010;Holzel et al, 2010;Jindal et al, 2006). These results suggest that the development of MLS B resistance can be influenced by historical exposure of the seed sludge to antimicrobials and antimicrobial resistant microorganisms and the presence of antimicrobial resistant microorganisms in the influent.…”
Section: Mls B Resistancesupporting
confidence: 62%
See 1 more Smart Citation
“…Angenent et al (2008) reported an increase in MLS B resistance in an ASBR treating swine waste but attributed their results to the enrichment with resistant bacteria present in the reactor feed. Occurrence of macrolide resistant organisms in swine waste has been reported previously (Chen et al, 2010;Holzel et al, 2010;Jindal et al, 2006). These results suggest that the development of MLS B resistance can be influenced by historical exposure of the seed sludge to antimicrobials and antimicrobial resistant microorganisms and the presence of antimicrobial resistant microorganisms in the influent.…”
Section: Mls B Resistancesupporting
confidence: 62%
“…Waste streams from hospitals, animal husbandry, and pharmaceutical production facilities contain elevated concentrations of antimicrobials (Campagnolo et al, 2002;Kummerer, 2001;Zilles et al, 2005) and are commonly treated in systems that rely on biological processes. Acceptable treatment performance has been reported in anaerobic lagoons treating manure with concentrations of antimicrobials that would inhibit sensitive microorganisms (Jindal et al, 2006;Zilles et al, 2005), but the mechanism(s) for maintaining biological activity in the presence of antimicrobials and the associated questions of how and when antimicrobial resistance develops are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Bacitracin A, chlortetracycline, and tylosin are antimicrobials commonly used in swine production (Cromwell, 2002;Jindal et al, 2006) and antimicrobial excretion rates of up to 90% in urine and 75% in feces have been reported (Halling-Sørensen et al, 2001). Swine produced at confined animal feeding operations (CAFOs) typically use one of three waste handling systems: flush systems, pit recharge, or deep pits (Sarmah et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The application of animal waste (biosolids) to agricultural soils (as soil conditioner) is commonly practised in the United States, Europe and Australia [47], and this acts as an entry point of both antibiotics and genetic resistance determinants into the environment [7,29,48]. Enteric bacteria can remain persistent in the environment for weeks to months, depending on species and temperature.…”
Section: Soil-borne Resistancementioning
confidence: 99%